Effects of Corn Stalk Fly Ash (CSFA) on the Mechanical and Deformation Properties of Cemented Coal Gangue Backfill. (11th February 2020) - Qi, Tingye; Wang, Haochen; Feng, Guorui; Du, Xianjie; Wang, Zehua; Zhang, Shufeng
Abstract : To reduce the amount of cement used in cemented coal gangue backfill (CCGB, a mixture of coal gangue, cement, fly ash, and water), mechanical and deformation properties of CCGB in which CSFA partially replaces the cement (0, 10, 20, 30, and 40 wt%) were studied. Compressive strength, acoustic emission during uniaxial loading, shear strength, and drying shrinkage were analysed. The compressive strength, shear strength, and drying shrinkage tests were performed at different curing times. The results showed that cemented coal gangue and corn stalk fly ash backfill (CGCAB) presented better performance, and the CGCAB with a 20% substitution rate had the best performance at day 28. Despite having the largest drying shrinkage value, 20% is the best choice for the substitution rate of CSFA. A 20% CSFA addition can enhance the bearing capacity of CGCAB and improve its failure mode, which is of great significance to support the upper overburden load and maintain the surface stability of the goaf.